2010
DOI: 10.1590/s0004-282x2010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of parafunctional habits and temporomandibular dysfunction symptoms in patients attending a tertiary headache clinic

Abstract: Objetive: To investigate the most prevalent forms of headache in a tertiary outpatient service, and to assess the frequency of associated parafunctional habits and temporo mandibular dysfunction symptoms (TMD). Method: All new patients referred to the Headache Outpatient Service in UNIMES during 2008 were prospectively assessed by the neurologist and the dental surgeon. results: Eighty new patients were assessed; chronic migraine and episodic migraine without aura were the most prevalent conditions, accounting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
4
12
0
6
Order By: Relevance
“…Menstrual migraine is well known to be more severe and refractory to treatment than non-menstrual migraine 10,24 , and a limitation of our study was not to characterize this migraine subgroup, since this would require longitudinal follow-up and use of dairies. We found strong association between migraine and TMD pain, as previously described 10,[12][13][14][15][16][17][18][19][20] . Gonçalves et al, in a population-based study, found that TMD symptoms are more likely to occur among those who present any headache type.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Menstrual migraine is well known to be more severe and refractory to treatment than non-menstrual migraine 10,24 , and a limitation of our study was not to characterize this migraine subgroup, since this would require longitudinal follow-up and use of dairies. We found strong association between migraine and TMD pain, as previously described 10,[12][13][14][15][16][17][18][19][20] . Gonçalves et al, in a population-based study, found that TMD symptoms are more likely to occur among those who present any headache type.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, TMD is a risk factor for increased headache frequency 10,[12][13][14][15][16][17][18][19][20] . Nonetheless, as with many of the identified risk factors for increased migraine frequency, most of the studies diagnosed both migraine and TMD based on self-reported symptoms or on questionnaires.…”
mentioning
confidence: 99%
“…Additionally, the clinical signs of TMD, such as tenderness in masticatory muscles and TMJ pain were also statically more common in headache patients, especially those ones with CDH in relation to subjects without headache, corroborating with others studies that also found a higher prevalence of masticatory muscle tenderness and TMJ pain in headache patients (5,7,10,15,24,25). …”
Section: Discussionsupporting
confidence: 88%
“…There is a significant positive association between temporomandibular pain and primary headaches . Headache patients were more likely to receive a diagnosis of myofascial pain (according to the RDC/TMD) than patients without headaches .…”
Section: Introductionmentioning
confidence: 99%